The angle is 80 degrees. The measure of an angle is the exact same as the angle measure of the included arc, so that makes angle BAC 80 degrees
<h2>
Answer:</h2>
A prism is a solid object having two identical bases, hence the same cross section along the length. Prism are called after the name of their base. A rectangular prism is a solid whose base is a rectangle. Multiplying the three dimensions of a rectangular prism: length, width and height, gives us the volume of a prism:
![V=L\times W\times H](https://tex.z-dn.net/?f=V%3DL%5Ctimes%20W%5Ctimes%20H)
FOR THE ORIGINAL PRISM WE HAVE THE FOLLOWING DIMENSIONS:
![L=14cm \\ \\ W=6cm \\ \\ H=3cm](https://tex.z-dn.net/?f=L%3D14cm%20%5C%5C%20%5C%5C%20W%3D6cm%20%5C%5C%20%5C%5C%20H%3D3cm)
In fact, the volume is
because:
![V=14\times 6\times 3 \therefore V=252cm^3](https://tex.z-dn.net/?f=V%3D14%5Ctimes%206%5Ctimes%203%20%5Ctherefore%20V%3D252cm%5E3)
Now the height of the prism was changed from 3 centimeters to 6 centimeters to create a new rectangular prism, therefore:
FOR THE NEW PRISM WE HAVE THE FOLLOWING DIMENSIONS:
![L=14cm \\ \\ W=6cm \\ \\ H=6cm](https://tex.z-dn.net/?f=L%3D14cm%20%5C%5C%20%5C%5C%20W%3D6cm%20%5C%5C%20%5C%5C%20H%3D6cm)
So the new volume is:
![V=14\times 6\times 6 \therefore V=504cm^3](https://tex.z-dn.net/?f=V%3D14%5Ctimes%206%5Ctimes%206%20%5Ctherefore%20V%3D504cm%5E3)
<h3><em>What do we know about the volume of the new prism?</em></h3>
<em>Well, the volume has increased from </em>
<em>and since</em>
<em>we can say that the new volume is two times the original volume.</em>
Answer:
97m
Step-by-step explanation:
From the image below we solve using pythagoras's theorem
x^2 = 72^2 + 65^2
x^2 = 5184 + 4225
x^2 = 9408
x = 97 m.
Further explanation is shown 8n the image.
I'm pretty sure you just multiply the 1 1/4 by 3 because if 1 1/4 makes 10 muffins you need to make 3 more dozens so 1 1/4 times 3 equals 3.75
Answer:
<h2>4x⁴yz - 16y³z = 4yz(x² - 2y)(x² + 2y)</h2>
Step-by-step explanation:
![4x^4yz-16y^3z\\\\4x^4yz=4yz\cdot x^4\\\\16y^3z=4yz\cdot4y^2\\\\4x^4yz-16y^3z=4yz\cdot x^4-4yz\cdot4y^2=4yz(x^4-4y^2)\\\\x^4-4y^2=x^{2\cdot2}-2^2y^2=(x^2)^2-(2y)^2=(x^2-2y)(x^2+2y)\\\\Used:\\\\(a^n)^m=a^{nm}\\\\(ab)^n=a^nb^n\\\\a^2-b^2=(a-b)(a+b)\\\\4x^4yz-16y^3z=4yz(x^2-2y)(x^2+2y)](https://tex.z-dn.net/?f=4x%5E4yz-16y%5E3z%5C%5C%5C%5C4x%5E4yz%3D4yz%5Ccdot%20x%5E4%5C%5C%5C%5C16y%5E3z%3D4yz%5Ccdot4y%5E2%5C%5C%5C%5C4x%5E4yz-16y%5E3z%3D4yz%5Ccdot%20x%5E4-4yz%5Ccdot4y%5E2%3D4yz%28x%5E4-4y%5E2%29%5C%5C%5C%5Cx%5E4-4y%5E2%3Dx%5E%7B2%5Ccdot2%7D-2%5E2y%5E2%3D%28x%5E2%29%5E2-%282y%29%5E2%3D%28x%5E2-2y%29%28x%5E2%2B2y%29%5C%5C%5C%5CUsed%3A%5C%5C%5C%5C%28a%5En%29%5Em%3Da%5E%7Bnm%7D%5C%5C%5C%5C%28ab%29%5En%3Da%5Enb%5En%5C%5C%5C%5Ca%5E2-b%5E2%3D%28a-b%29%28a%2Bb%29%5C%5C%5C%5C4x%5E4yz-16y%5E3z%3D4yz%28x%5E2-2y%29%28x%5E2%2B2y%29)